Avaliação da sustentabilidade do desenvolvimento do município de Altamira (PA) sob a ótica dos Objetivos de Desenvolvimento Sustentável (Agenda 2030) das Nações Unidas utilizando a ferramenta barômetro da sustentabilidade - QUINTELA, Patrick Diniz Alves (Universidade Federal do Pará, 2025)
In recent decades, there have been more debates related to environmental damage that has been causing changes at a global level, according to the understanding of the finitude of natural resources. The Amazon figures as a protagonist when thinking about the protection of the global ecological heritage. Given its importance, the largest tropical forest in the world has been contemplated with several projections to preserve it. Altamira is a municipality in the center of the Legal Amazon and figures as a reflection of the main problems faced in this territory. Traditional populations coexist with agribusiness, and both are flooded by large projects, although one side benefits more. The rural and the urban areas also provide the municipality with a contrast that makes it especially difficult to point out or even define what would be sustainable. Despite the numerous conflicts that do not allow this territory to homogenize, this thesis sought to carry out a socio-environmental analysis based on the axes of human well-being and environmental well-being, of multidisciplinary nature, for the municipality of Altamira, based on the Sustainable Development Goals (SDGs) launched in 2015 by the United Nations Development Program (UNDP) and thus evaluate the main obstacles to the full sustainable development of the municipality. To obtain the results, the methodology used is called the Barometer of Sustainability (BS) and is the result of the major global conventions that debate the courses that take the social, economic, and environmental dimensions. The results obtained showed that Altamira has an intermediate level for sustainability and reflects the need for a special look of the government to the indicators related to the great socio-economic axis as well as the need for the elaboration of strategies to remedy and contain the problems related to the great environmental axis. It was then concluded that the municipality of Altamira is far from achieving the goals established by the 2030 agenda, but that it presents breath and has demonstrated subtle changes that are moving towards achieving such objectives. Finally, although limited, this thesis was intended to date a result and create a basis for future research that aims to analyze, add, or even refute results obtained for the municipality of Altamira.